لجنة الحقيقة والمصالحة في دولة جنوب افريقيا (Journal of the College of Basic Education, 2022)
South Africa's experience, in countering the legacy of apartheid, played an important role in developing transitional justice. In order to make this experiment a success, Nelson Mandela did his best to move towards a reconciliation process. In the field of national reconciliation, South Africa is considered one of the most successful countries in the world, and it is also a model that can be emulated when discussing the experience of democratic transition, and according to international estimates, Mandela's success in this experiment made his country economically on the throne of the African continent. When he took office in 1994, Public pressure increased on him, demanding that he hold accountable all those who persecuted, repressed, and committed crimes against innocent black citizens. But he was able to overcome this pressure and crisis, and completely solve the problem through the formation of the so-called (Truth and Reconciliation) Commission. The idea of ​​the commission was based on the criminals ’recognition of their human rights violations and acts, in exchange for a request for amnesty. The commission's mandate was to grant pardons and compensate victims and their families rather than bring the perpetrators to justice.